Rancang Bangun Portal Website Sepakbola SSB Elang Muda Brimob Banyumas - wahyu nugroho (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2021)
The development of football in the Banyumas area continues to develop along with the existence of several SSB that are spread in almost every sub-district in the Banyumas area, this development cannot be separated from the role of information technology, almost all SSB in the Banyumas area have information media to attract public interest, especially in SSB Elang Muda Brimob Banyumas. The lack of development of access to information at SSB Elang Muda Brimob Banyumas attracted researchers to develop website-based access to information systems at SSB Elang Muda Brimob Banyumas with the aim of facilitating access to information and services to the community, increasing promotion in the field of sports using system design methods, field observations , as well as literature study, the database used in this system uses MySql to store player data. The results of this study resulted in a website-based application program which initially used a manual data input system then developed into a website.